Establishment of an indirect ELISA detection method for porcine reproductive and respiratory syndrome virus NSP4 - Zhao, Mengmeng; Lv, Chen; Pang, Jiankun; Yang, Zhiyu; Sha, Huiyang (Frontiers in Microbiology, 2025)
The non-structural protein 4 (NSP4) of porcine reproductive and respiratory syndrome virus (PRRSV) is equipped with 3C-like serine protease (3CLSP) activity, influencing crucial aspects such as virus replication, host IFN-β suppression, host cell apoptosis induction, and PRRSV detection facilitation. In response to wild or attenuated PRRSV strains, antibodies against non-structural proteins are generated, while inactivated vaccines fail to elicit such responses. Employing the Enzyme-Linked Immunosorbent Assay (ELISA) method targeting non-structural proteins helps discern the immune effects of inactivated versus wild or attenuated vaccine strains. The study focused on the NSP4 protein from the PRRSV XH-GD strain (GenBank No. EU624117.1), which was cloned, expressed, and leveraged as a coating protein for establishing an indirect enzyme-linked immunosorbent assay (ELISA) detection method. This method showcased outstanding specificity, repeatability, and sensitivity, exhibiting a notable agreement rate of 91.74% with the PRRSV IDEXX ELISA kit. The successful development of the NSP4 indirect ELISA not only supports the detection of PRRSV antibodies but also provides a robust platform for ongoing antibody monitoring in pig farming. Utilizing PRRSV NSP4 for ELISA antibody detection offers a more sustainable approach for continuous surveillance. The high agreement between this method and commercial kits lays a solid groundwork for effectively differentiating between inactivated and attenuated vaccines, enhancing the management and monitoring of PRRSV in pig populations.